2009
DOI: 10.1001/archoto.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Carcinoma of the Neck of Unknown Primary Origin: Evolution and Efficacy of the Modern Workup

Abstract: Diagnostic workup including PET-CT, alongside panendoscopy with directed biopsies including bilateral tonsillectomy, offers the greatest likelihood of successfully identifying occult primary tumor location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 14 publications
6
155
1
9
Order By: Relevance
“…In the search for a primary tumor in the head and neck, a CT scan may be either complemented or supplanted by MRI with gadolinium contrast, which exhibits superior soft tissue resolution, particularly for the evaluation of the nasopharynx or oropharynx. The potential of CT, MRI or both to detect a primary tumor ranges from 9.3 to 23% (3,18,19), rising to 60% when suspicious radiological findings direct subsequent endoscopic biopsies (20). Over the last 2 decades, positron emission tomography (PET) has also been used in patients with CUP.…”
Section: Diagnostic Work-upmentioning
confidence: 99%
“…In the search for a primary tumor in the head and neck, a CT scan may be either complemented or supplanted by MRI with gadolinium contrast, which exhibits superior soft tissue resolution, particularly for the evaluation of the nasopharynx or oropharynx. The potential of CT, MRI or both to detect a primary tumor ranges from 9.3 to 23% (3,18,19), rising to 60% when suspicious radiological findings direct subsequent endoscopic biopsies (20). Over the last 2 decades, positron emission tomography (PET) has also been used in patients with CUP.…”
Section: Diagnostic Work-upmentioning
confidence: 99%
“…Although recent molecular studies showed promising results for identifying the primary site [18], the current standard HNSCCUP workup includes a combination of CT or MRI, positron emission tomography (PET), and panendoscopy (nasopharyngoscopy, laryngoscopy, bronchoscopy and esophagoscopy) with biopsies from several mucosal sites (base of tongue, nasopharynx, piriform sinus). The rate of success in identifying the primary tumor is variable, likely related to the diagnostic workup strategy, primary tumor size, radiological and pathological thoroughness, the quantity and quality of the tissue sampled and, even in recent studies, it was reported to be only 45-59% [19,20]. In both series, the most commonly identified tumors after complete workup were in oropharynx.…”
Section: Discussionmentioning
confidence: 90%
“…A quick, inexpensive, procedure with high spatial resolution is the contrast-enhanced CT-scan from the skull base to clavicles, complemented or substituted by a gadolinium contrast-enhanced MRI with superior soft tissue resolution [43]. In case of a cervical lymph node metastasis, the chance for CT, MRI or both to detect the primary site ranges from 9 to 23% [7,[47][48][49]. When suspicious findings on imaging are used to guide biopsy, the chance to find the primary tumor rises up to 60% [50].…”
Section: Imagingmentioning
confidence: 99%